Cosmos-life-consciousness IV - Fabio Soares Pereira, Elcio (Seven Editora, 2023)
In the INTRODUCTION, comments on his published works are made. The frontier reached so far was the development of a genetic model for the generation of atoms. Some basic concepts are presented for the understanding of what is called “relevant relative information”, a concept of paramount importance for understanding the process of consciousness formation. In DISCUSSION AND CONCLUSION, admitting the veracity of the genetic model for the generation of atoms, he formulates new very instigating questions, presenting hypotheses to answer them. Of the hypotheses formulated, the most intriguing is that structures similar to biological RNA and DNA have been formed in the cosmos. Discusses some conditions necessary for their formation and possible consequences arising from them. It shows that the existence of these structures answers some questions still unanswered and finally makes some considerations about the beginning of the cosmos. DOI: https://doi.org/10.56238/devopinterscie-086